Pengaruh Media Podcast Sains Sahabat di Era Pandemi Sebagai Teman Belajar IPA SMP terhadap Hasil Belajar Pasca Covid: The impact of “Sains Sahabat Podcast” as science study partner to the result of Covid pasca pandemic - Zulfa - Ihzani; Fitria Eka Wulandari (UNIB Press, 2022)
The study was intended to identify the effects of the media podcast as a friend to study high school science on post-covid study. Quantitative research is the type of research used in pre-experiment design, one group preposttest involving class vii at the 1st state junior temple in sidoarjo. Research instruments of cognitive learning tests. Data is analyzed by a normalized n-gain method. Based on data analysis, the pretest value obtained before using the podcast is 59. For the posttest score following the application of the media podcast is 77. The value of a difference between pretest and posttest in 18 and with a gain index of 0.47 is moderate. This suggests that the use of podcast in science studies has affected students' cognitive learning results, as there has been an increase in posttest and pretest scores.